The development of continuous positive airway pressure: an interview with Dr. George Gregory. Issue 1 (21st November 2012) - Mai, Christine L.; Yaster, Myron; Firth, Paul; Morton, Neil
Summary George Gregory, M.D. (1934‐), Professor Emeritus at the University of California, San Francisco, has made numerous contributions to neonatology and pediatric anesthesia through his research efforts and authoritative textbook, Gregory's Pediatric Anesthesia. However he identified his defining moment as the occasion he saved the life of an infant suffering from neonatal respiratory distress syndrome by using continuous positive airway pressure (CPAP) ventilation. The development of CPAP by Gregory revolutionized the treatment of premature infants with respiratory failure. Prior to the creation of this treatment, the mortality rate of neonates with respiratory distress syndrome was >50%. The innovation markedly improved the ventilation of infants with respiratory distress and led to significant improvements in survival rates. Based on an interview with Dr. Gregory, this article describes the discovery of CPAP and reviews his career in advancing pediatric anesthesia and critical care medicine.